SMU rebrands continuing legal education arm as SMU Law Academy - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
In line with the nationwide SkillsFuture movement, and to support current and future training and development needs of Singapore’s legal fraternity Singapore, Singapore Management University (SMU) today officially announced the rebranding of its School of Law’s Continuing Legal Education (CLE) arm as SMU Law Academy. The SMU School of Law has, since 2010, been a Singapore Institute of Legal Education (SILE) -accredited service provider of Continuing Professional Development (CPD). To date, the law school's CLE arm has an established track record of providing the legal profession with high quality seminars and auditing programmes to stay informed about contemporary legal developments, with a total of about 1,000 participants taking up its collection of some 30 seminars and workshops organised each year.